Resistotyping of Candida albicans isolated from sputum samples of patients attending TB clinics in and around Chidambaram - V. Udhaya, Y. Lakshmi Sarayu, K.K. Prasobh (Recent Research in Science and Technology, 2009)
Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Ã‚Â Resistotyping was first developed for strain delineation, pathogenesis, or epidemiological studies. This depends on the ability of the strains to grow on agar plates containing various dilutions of toxic chemicals. There are many resistotyping methods and modified techniques were used by the authors to carry out the typing of clinical isolates of Candida. We performed resistotyping of 350 Candida albicans (isolated from the sputum of TB clinic attendees) with modified technique and could able to obtained four (04) different resistotypes among Ã¢â‚¬â€œB–F- resistotypes was found to be the predominant Candida albicans resistotypes we recorded. From our one year study period from June 2007 to May 2008, we concluded that the Candida albicans resistotypes Ã¢â‚¬â€œB–F- was the most commonly found resistotype in the specified areas of Cudallore district of Tamilnadu, India.